Aplicação de doses de selenato de sódio no solo e micorriza arbuscular no teor de Se em soja e braquiária - Bamberg, Soraya Marx (2015)
Owing to selenium essentiality for humans and animals and the low levels evidenced in soils and consequently in Brazilian foods, the strategy to use mycorrhiza as an attempt to greater concentration of this element in soybeans and brachiaria grass, is the target of this work. Was evaluated the effects of this symbiosis at increasing concentration of this element in the edible parts of soybean and Brachiaria forage, Thereunto, was cultivated in a greenhouse soybean and brachiaria grass in a completely randomized design, in 5x2 factorial arrangement with three replications by 60 and 90 days for Brachiaria grass and soybean, respectively. Were used 5 doses of sodium selenate applied to the soil (0,0; 0,5; 1,0; 3,0 e 6,0 mg kg-1 for brachiaria and 0,0; 0,5; 1,0; 2,0 e 3,0 mg kg-1 for soybean) with the presence and absence of mycorrhiza (inoculum containing Acaulospora morrowiae and Claroideoglomus etunicatum) in each plants studied. Both species responded to selenate doses applied. We obtained a higher production in soybeans at 1.89 mg kg-1 dose, in shoot brachiaria at the 6.0 mg kg-1 dose in the presence of mycorrhiza and 2.92 mg kg-1 in the absence. In soybeans there was a mycorrhizal effect on the selenium content only at root and shoot dry matter production, in grains was observed only significant effect of doses. Both plant species had plant content enhanced as well as plant growth by increase doses when applied to the soil. The levels found in brachiaria exceeded the maximum desired for consumption from 0.29 mg kg-1 dose. The application of high Se in doses in brachiaria showed a toxic effect, but mycorrhiza symbiosis conferred a protective effect on plant growth. The levels found in soybeans were satisfactory for human and animal consumption at 3.0 mg kg-1 dose, being influenced only by the applied doses, without mycorrhiza effect.